Disrupsi Teknologi Keuangan Islam dan Regulasi Fintech - Siska Nurpitasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Disruption of Islamic financial institutions in technology has become a necessity due to developments in technology and information. This development is expected to make it easier for sharia financial institutions to provide operational services. Collaboration with financial technology (fintech) is a good thing in its development. Fintech, which was originally a rival, has changed its paradigm to become a partner. This is a phenomenon why the revolution in technology and fintech collaboration is very important, so that Islamic financial institutions are aware of these developments. And in tandem with facilitating institutions to socialize and regulate technology and fintech.